1987
DOI: 10.1177/0310057x8701500210
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Midazolam and Diazepam for Induction of Anaesthesia in High-Risk Patients

Abstract: Fifty ASA Class JII patients were divided randomly into two equal groups for induction of anaesthesia with diazepam 0.25 mg / kg, or midazolam 0.15 mg / kg. All subjects were premedicated with a narcotic and monitored by ECG, radial arterial catheter and a spirometer for measurement of minute ventilation. The QF interval (time period from the Q wave of the ECG to thefoot of the radial artery pulse), mean arterial pressure, heart rate and minute ventilation were recorded before, during and immediately after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…9 In an un-cooperative child, drug dosage if accidentally increased or decreased may make the child unsuitable for anaesthesia. 10 A palatable oral preparation is usually acceptable to child and fluctuation of dosage being minimum; this cannot produce unpredictable side effects.…”
Section: Discussionmentioning
confidence: 99%
“…9 In an un-cooperative child, drug dosage if accidentally increased or decreased may make the child unsuitable for anaesthesia. 10 A palatable oral preparation is usually acceptable to child and fluctuation of dosage being minimum; this cannot produce unpredictable side effects.…”
Section: Discussionmentioning
confidence: 99%
“…In relatively healthy, normovolemic patients, midazolam at these dosages causes either no change or only modest decreases in mean arterial pressure (MAP) (#10 mm Hg). [24][25][26][27][28][29][30][31][32][33][34][35][36] In studies of patients with limited cardiac reserve, induction with 0.2 to 0.3 mg/ kg of midazolam causes mean decreases in MAP ranging from about 10 mm Hg to about 20 mm Hg. 16,[37][38][39][40] These modest hemodynamic effects were seen using dosages of midazolam that were two to three times the dose (0.1 mg/kg) we used as our cutoff for underdosing, and four to six times the mean dose we observed emergency physicians using in adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of thrombophlebitis was similar to that reported by Reves et al 1979, Reitan et al 1987, Abraham and Kaur 1997. 8,9,10 Gamble et al 2001, found thrombosis and thrombophlebitis in 2 patients each after midazolam and propofol between 7-10 days after surgery, even though there was no sign of venous irritation in the ¿ rst week. 11 Patient acceptance of anesthesia was good in 75% patients in midazolam group whereas the patient's acceptance in propofol group was 45.8% Patient's acceptance of anesthesia was satisfactory in 54.2 in propofol whereas it was 25% in midazolam group.…”
Section: Post Operative Featuresmentioning
confidence: 99%